Implementation of Independence Character Education in Madrasah - Fakhrurrazi Fakhrurrazi; Hamzah Hamzah; Herra Herryani; Herlan Suherlan; Desy Desy (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to explore information related to the implementation of self-reliance character education through the creation of a school climate in Madrasah Tsanawiyah Dayah Darul Huda, Langsa City. Through this research, it is hoped that various policies and strategies carried out by Madrasah Tsanawiyah will be found in an effort to internalize the values of the character of independence through the creation of a school climate.This research is a descriptive research with a qualitative approach. Data collection techniques used in this study were observation, interviews, and documentation. The technique of checking the validity of the data used is the method triangulation technique. The analytical technique used in this research is inductive analysis technique, which is an analysis that starts from the data and leads to general conclusions. The steps of data analysis include: data reduction, unitization and categorization, data display, and drawing conclusions. The findings in the study show the following results: first, that in the context of implementing self-reliance character education in Madrasah Tsanawiyah Dayah Darul Huda Langsa City has a policy to build independence in students (santri) both independence in terms of learning, self-regulation independence, independence in managing time while students are in the Madrasah environment. Second, in an effort to implement independence character education in the learning process the teacher uses the following strategies: 1) assignments that require students to independently utilize existing learning resources in the dayah and madrasah environment, 2) make learning contracts, and 3) integrate independence character education in the learning process. teaching and learning in the classroom. Third, related to the obstacles experienced by madrasas in implementing independence character education, namely the lack of consistency of parents, and the presence of several teachers who have not integrated independence character education in the learning process.